Generation of decellularized human brain tissue for investigating cell-matrix interactions: a proof-of-concept study - Bueno, Roemel Jeusep; Fernández-Zapata, Camila; Salla, Maren; Campo Garcia, Juliana; Alacam, Aylin; Klein, Oliver; Böttcher, Chotima; Radbruch, Helena; Paul, Friedemann; Starossom, Sarah C.; Silva, Rafaela V.; Infante-Duarte, Carmen (Frontiers in Bioengineering and Biotechnology, 2025)
The brain extracellular matrix (ECM) regulates myelin repair and regeneration following a demyelinating event by interacting with neuronal progenitors and immune cells. Therefore, generation and characterization of decellularized human brain tissue (DHBT) in regions with distinct neuroregenerative capacities are essential to determine factors modulating the cellular regenerative behavior. We have established an effective decellularization protocol for the human neural stem cell (NSC)-rich subventricular zone (SVZ) as well as, frontal cortex (FC) and white matter (WM), and defined region-specific matrisomes with comparative proteomics. Subsequently, as proof-of-concept, survival and differentiation of NSCs and monocytes within the DHBT were investigated. The proteomic analysis of the DHBT confirmed the retention of matrisome proteins such as COL4A1, FBB, NCAN, ANXA2. Unique to the SVZ were LGI3 and C1QB, while annexins, S100A and TGM2 were found in FC; S100B was exclusive to the WM. NSCs cultured within WM and FC acquired an astrocytic phenotype, but both astrocytic and oligodendrocytic phenotypes were promoted by the SVZ DHBT. Moreover, imaging mass cytometry analysis indicated an anti-inflammatory phenotype differentiation of monocytes seeded on SVZ and WM. Thus, the established model is suitable for investigation of ECM properties and assessment of cell-matrix interactions.